THE EFFECT OF INTEGRATIVE BEHAVIORAL THERAPY VERSUS EMOTION-FOCUSED THERAPY FOR COUPLES: A META-ANALYSIS - PINTEA, Sebastian; POP, Roxana; KALLAY, Eva (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2019)
The negative effects of a dysfunctional couple’s relationship influence the partners to look for a form of therapy that can help them improve their relationship. The present paper integrates the research data for two of the most studied couple therapies: Integrative Behavioral Couple Therapy and Emotion-Focused Therapy. The study compares the two therapies and integrates in a meta-analysis the outcomes of 15 studies (N=373 couples). Results show a high effect for both forms of therapy, with no significant differences between them. The moderating role of the type of outcome, the couples’ characteristics, and the sample’s demographic characteristics, were explored, the results proving that the investigated couple therapies have the same strong effect, irrespective of all those factors.